Windows cleaner: a free operating system gains fans in Asia. - Dolven, Ben (Far Eastern Economic Review, 1998)
The writer describes a free computer operating system that is becoming popular in Asia. The Linux system constitutes the basic software that enables a computer to run programs and is free to anyone who downloads it from the Internet. While Microsoft assiduously guards its programs and intellectual-property rights, Linux does not claim any, and the system has developed by enthusiasts tinkering with it, making improvements, and posting their own Linux programs on Web pages. Its affordability is a key attraction: Linux is not only free—it allows companies to economize on hardware costs because it runs comfortably on old, 1980s bargain-basement computers.